Muramyl dipeptide potentiates Staphylococcus aureus lipoteichoic acid-induced nitric oxide production via TLR2/NOD2/PAFR signaling pathways - Im, Jintaek; Jeon, Jun Ho; Lee, Dongwook; Park, Jeong Woo; Jun, Woohyung; Lim, Suwon; Park, Ok-Jin; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Immunology, 2024)
Lipoteichoic acid (LTA) and peptidoglycan (PGN) are considered as key virulence factors of Staphylococcus aureus, which is a representative sepsis-causing Gram-positive pathogen. However, cooperative effect of S. aureus LTA and PGN on nitric oxide (NO) production is still unclear despite the pivotal roles of NO in initiation and progression of sepsis. We here evaluated the cooperative effects of S. aureus LTA (SaLTA) and muramyl dipeptide (MDP), the minimal structure of PGN, on NO production in both a mouse macrophage-like cell line, RAW 264.7 and mouse bone marrow-derived macrophages (BMMs). Although MDP alone did not affect NO production, MDP potently enhanced SaLTA-induced NO production via the expression of inducible NO synthases. The enhanced NO production was ameliorated in BMMs from TLR2-, CD14-, MyD88-, and NOD2-deficient mice. Moreover, the augmented SaLTA-induced NO production by MDP was attenuated by inhibitors specific for PAFR and MAP kinases. Furthermore, MDP also potently increased SaLTA-induced activities of STAT1, NF-κB, and AP-1 transcription factors, and specific inhibitors for these transcription factors suppressed the elevated NO production. Collectively, these results demonstrated that MDP potentiates SaLTA-induced NO production via TLR2/NOD2/PAFR, MAP kinases signaling axis, resulting in the activation of NF-κB, AP-1 and STAT1 transcription factors.